A model for the adoption and effective utilization of ICTs in commercial agriculture in Zimbabwe - Gavai, Petros; Musungwini, Samuel; Mugoniwa, Beauty (Czech Society of Systems Integration, 2019)
The turn of the 21 st century saw Zimbabwe embarking on the Fast Track Land Reform Programme (FTLRP) which promoted new commercial farmers in the agricultural sector in the country. These new commercial farmers in post-FTLRP utilise basic ICTs like mobile phones which have less significance in revitalizing their farming activities. This study seeks to establish reasons behind the low level of ICT adoption and underutilisation by new commercial farmers in Zimbabwe. Using the critical realism philosophical paradigm, the study proposes a model for the adoption as well as effective utilisation of ICTs in commercial agriculture in the country. It is further argued that the adoption of ICTs in commercial agriculture remains a challenge in Zimbabwe especially in the post land reform era where farmers concentrate on using basic farming equipment such as pivots, telecommunication lines and water pipes previously put in place by former owners most of which are now vandalized. It is hoped that the new farmers in order to adopt new technology in farming should be trained through workshop and seminars on the use of ICTs for effective commercial agriculture. The Government of Zimbabwe is further challenged to review the land ownership policy especially on timely processing of ownership documents.